2020
DOI: 10.1089/neur.2020.0009
|View full text |Cite
|
Sign up to set email alerts
|

XGBoost, a Machine Learning Method, Predicts Neurological Recovery in Patients with Cervical Spinal Cord Injury

Abstract: The accurate prediction of neurological outcomes in patients with cervical spinal cord injury (SCI) is difficult because of heterogeneity in patient characteristics, treatment strategies, and radiographic findings. Although machine learning algorithms may increase the accuracy of outcome predictions in various fields, limited information is available on their efficacy in the management of SCI. We analyzed data from 165 patients with cervical SCI, and extracted important factors for predicting prognoses. Extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Alongside the relatively limited sample size of available clinical SCI datasets, the variety of SCI characteristics presents significant challenges for reproducible identification of patient outcome predictors despite the volume of data collected throughout patient hospitalization and treatment [ 20 ]. Various prognostic models for SCI outcome have been developed with algorithms ranging from logistic regression to extreme gradient boosted (XGB) trees and convolutional neural networks [ 12 , 21 , 22 ]. While such studies bear potential for informing clinical care, algorithm selection in many SCI ML studies have primarily depended on the researchers’ familiarity with specific ML algorithms, and prediction accuracy remains the primary metric for comparing models [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside the relatively limited sample size of available clinical SCI datasets, the variety of SCI characteristics presents significant challenges for reproducible identification of patient outcome predictors despite the volume of data collected throughout patient hospitalization and treatment [ 20 ]. Various prognostic models for SCI outcome have been developed with algorithms ranging from logistic regression to extreme gradient boosted (XGB) trees and convolutional neural networks [ 12 , 21 , 22 ]. While such studies bear potential for informing clinical care, algorithm selection in many SCI ML studies have primarily depended on the researchers’ familiarity with specific ML algorithms, and prediction accuracy remains the primary metric for comparing models [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inoue and colleagues proposed models predicting neurological outcomes 6 months after injury based on the binary classi cation of AIS grade A/B/C or D/E, and XGBoost had the highest accuracy (81.1%). 7 For predicting reacquisition of walking ability, the predictive model with a binary classi cation of improvement to more than AIS grade D is useful. However, not only predicting motor ability but also predicting recovery of one AIS grade or two AIS grades (eg, AIS grade A to B or AIS grade A to C), is considered clinically meaningful neurological recovery from the patient's perspective.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that ML models were useful for predicting neurological improvements in patients with CSCI. 7 However, it included cases that received both surgical and conservative treatment, and the outcome of the prediction was a binary classi cation of the American Spinal Injury Association (ASIA) Impairment Scale (AIS), grades A/B/C or D/E. Several studies reported that early surgery within 24 hours after injury has a signi cant impact on the neurological prognosis of spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to clarify the prevalence, severity and characteristics of insomnia in breast cancer survivors and to determine the clinical characteristics associated with the comorbidity. We also developed a classifier that predicts the comorbid insomnia using two machine learning algorithms, namely, the L2 penalized logistic regression model and the XGBoost model ( 12 ). Furthermore, we used the RuleFit algorithm to extract the hidden rules for segments at high risk of comorbid insomnia.…”
Section: Introductionmentioning
confidence: 99%